Analisa pengaruh variasi berat roller dengan pegas CVT terhadap kinerja mesin sepeda motor matic 113 cc - prastiyo, Adi; Irawan, Dwi; Ridhuan, Kemas (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2020)
As the emergence of vehicles that use the CVT transmission system (Countinuesly Variable Transmission) or better known as the automatic motor. The automatic motor has a CVT roller and spring. Roller weight is a weight balance bearing that is useful for pressing the inner wall of the primary pulley when high rotation occurs, and a CVT spring is a spring whose function is to return the secondary pulley to its initial position or the position of the outer belt. The purpose of this study was to determine the effect of CVT springs with roller weight on the performance of the 113 CC automatic motorcycle engine and the effect on specific fuel consumption. In this study the type of vehicle used is Yamaha Mio Sporty 113 CC motorcycle, and the variation of CVT springs with roller weight used is CVT Spring 2.26 N / mm, 2.45 N / mm, and 2.67 N / mm, with a roller weight of 7 grams, 10.5 grams and 14 grams. The testing method used is to test torque and power with dynotest tools to determine the torque and power obtained, as well as acceleration testing to determine the ratio of speed on each variation of CVT springs to roller weight, and specific fuel consumption. From the research that has been done, the results are for the highest torque value obtained in the CVT spring 2.26 N / mm with a 7 gram roller that is 6.14 Nm at 5095 engine rpm, and the highest power in the CVT spring 2.26 N / mm with 7 and 14 gram rollers are 4.9 Hp with a maximum engine rpm of 9250, the best acceleration on a 2.67 N / mm CVT spring with a 14 gram roller that is 201 meters away with 12.63 seconds, and specific fuel consumption is saved on a 2.26 N / mm CVT spring with a 7 gram roller which is 1.98 kg / hour or equivalent to 2.45 ml / s.